Hey, Al - Yorinks, Arthur; Egielski, Richard; Juvenile Collection (Library of Congress) (New York : Farrar, Straus and Giroux, 1986)
A city janitor and his treasured canine companion are transported by a large colorful bird to an island in the sky, where their comfortable paradise existence threatens to turn them into birds as well.
On jacket: The Caldecott medal.
Keywords: Birds -- Fiction; Caldecott Medal; Dogs -- Fiction; Imprints 20th century 1986; Juvenile literature -- New York (N.Y.) -- 1986.